Pengaruh Influencer Marketing dan Brand Image terhadap Minat Beli Produk Camille Beauty pada Mahasiswa Fakultas Ekonomi Universitas Al Washliyah Labuhan Batu - Aritonang, Ela Widiantari; Sukmal, Jeni; Rusdi, M. (VISA: Journal of Vision and Ideas, 2025)
This research aims to analyze the influence of influencer marketing and brand image on the purchase intention of Camille Beauty products among students of the Faculty of Economics at Universitas Al Washliyah Labuhanbatu. Employing a quantitative approach with a survey method, data from 50 student respondents were analyzed using multiple linear regression. The research findings indicate that both influencer marketing and brand image have a positive and significant partial effect on the purchase intention of Camille Beauty products.